رأي ابن خلدون في تأسيس الدولة وآثارها في الدول الإسلامية المعاصرة - Lanang Hutama Yurivda Hardian Mada; Moh. Mujibur Rohman (Indonesian Journal of Islamization Studies, 2024)
This article explores the contributions of Ibn Khaldun, a prominent Islamic scholar and the author of "al-Muqaddimah," widely regarded as the founder of sociology in Islam. The study employs a normative research method with an analytical and historical approach to examine his thoughts on statecraft, which are both conceptually rich and empirically grounded. Key findings include the Islamic concept of the state as a collective governed by a political system, Ibn Khaldun's role as a reformer integrating social issues into state formation, and his significant influence, especially in Arab countries and parts of Asia, on the development of sociopolitical thought